Tinjauan Yuridis Penggandaan Lagu secara Komersial dalam Wadah Media YouTube Tanpa Seizin Pemilik (Studi Putusan Nomor 26/Pdt.Sus-Hak Cipta/2021/PN Niaga Jkt.Pst jo. Putusan Mahkamah Agung Nomor 913 K/Pdt.Sus-HKI/2022) - Siti Kayla Haliza; Jelly Leviza; Aflah (CV Rewang Rencang, 2025)
Song commercialization on YouTube often violates copyright as unauthorized reproduction disregards creators' moral and economic rights. This normative descriptive research examines legal protection, perpetrator liability, and legal considerations in Decision 913K/Pdt.Sus-HKI/2022. Legal protection is implemented preventively through copyright registration and repressively through compensation claims and criminal charges. Unauthorized reproduction perpetrators face criminal sanctions up to 10 years imprisonment or Rp4 billion fine. The court's decision is deemed disproportionate in depicting creators' losses and inadequately reflects principles of justice and legal certainty.